Restrição alimentar intra-uterina e suas repercussões sobre o desenvolvimento da termorregulação da prole - Souza, Thais Ladeira Vieira de [UNIFESP] (2009)
Background: Previous study from our laboratory has shown that intrauterine food restriction (IUFR) delayed thermoregulation of the newborns. In neonates brown adipose tissue (BAT) is essential for thermogenesis mainly due to the presence of uncoupling proteins (UCPs) and their expression can be modified by action of hormones such as thyroid hormone, leptin and insulin, which can be affected by food restriction. The sarcoplasmic reticulum Ca++ ATPase, (SERCA1) recently identified in BAT may contribute to heat production. Aim: The aim of this study was to evaluate the protein expression of UCP1, UCP2, UCP3 and SERCA1 in BAT and UCP3 and SERCA1 in skeletal muscle (SM) and the plasmatic concentration of insulin, leptin, T3 and T4 of newborn rats exposed to IUFR. Methods: Female Wistar EPM-1 control rats received chow ad libitum during pregnancy period (C) and food-restricted rats (R) received 50% of the amount ingested by C. Fifteen hours after birth, newborns were weighted and sacrificed by decapitation. Blood was collected for determination of insulin, leptin, T3 and T4 by ELISA. BAT and SM were used for determination of protein expression (UCPs and SERCA1) by immunohistochemistry. Unpaired Student’s t-test was used for statistical analysis of the results (p<0,05). Results: R animals (n=16) showed a significant lower weight gain (g) during pregnancy when compared to C (n=16) (27,6 ± 3,8 and 109,0 ± 4,1). R pups (n=172) showed a significant reduction in their body weight (g) at birth when compared to C (n=169) (4,82 ± 0,05 and 5,83 ± 0,04); however, there was no reduction in number of pups per litter. IUFR caused a significant increase in the expression (pixels) of UCP1 and UCP2 in BAT of the pups (42% and 53% respectively). UCP3 and SERCA1 expression in BAT and SM showed no significant differences between groups. Plasmatic insulin (ng/ml) was significantly higher in R pups (n=8) when compared to C (n=13) (3,34 ± 0,78 and 1,17 ± 0,18) and T3 levels (ng/ml) was significantly lower in R pups (n=10) when compared to C (n=14) (0,82 ± 0,06 and 1,09 ± 0,08). No differences between groups were found for leptin (pg/ml) (R (n=8) 987,79 ± 261,08 and C (n=11) 1255,54 ± 392,37) and T4 (ng/ml) levels (R (n=10) 20,99 ± 3,74 and C (n=12) 16,00 ± 1,68). Conclusion: The delay in development of thermoregulation previously described in these animals appears not to result from impairment in thermogenesis, but from an increase in heat loss, since IUFR caused low birth weight in pups, leading to greater surface/ volume ratio. The higher expression of UCP1 and UCP2 in BAT showed by R pups possibly occurred as a compensatory mechanism to increase thermogenesis, which may have been modulated by hormonal regulation.